Molecular interaction of human acetylcholinesterase with trans-tephrostachin and derivatives for Alzheimer's disease. Issue 9 (September 2020) - Pitchai, Arjun; Rajaretinam, Rajesh Kannan; Mani, Rajasekar; Nagarajan, Nagasundaram
Abstract: Alzheimer's disease (AD), a neurodegenerative disorder affects more than 35 million people globally. Acetylcholinesterase suppression is the common approach to enhance the well-being of AD patients by increasing the duration of acetylcholine in the cholinergic synapses. Generally, herbal secondary metabolites are reported to be a major resource for acetylcholinesterase inhibitors (AChEIs). Trans -tephrostachin was reported from Tephrosia purpurea for AChE inhibition. Here, we report on the design, synthesis, and assessment of human acetylcholinesterase inhibitory activity from trans -tephrostachin derivatives or analogs as anti-AD agents. The five newly synthesized compounds 4a. 4b, 4c, 4d and 4e displayed potent inhibitory activities with IC50 values of 35.0, 35.6, 10.6, 10.3, and 28.1 μM respectively. AChE enzyme kinetic study was performed for the five derived compounds using the Ellman's method. The Lineweaver-Burk and the secondary plots revealed the mixed inhibition for 4a, 4c and 4d whereas 4b and 4e demonstrated competitive inhibition. Molecular docking and molecular dynamics simulations showed the derivatives or analogs of trans -tephrostachin attained a high binding affinity and efficacy than the standard drug. In conclusion, trans -tephrostachin and its derivative compounds could become effective agents for further drug development to treat AD. Abstract : Acetylcholinesterase (AChE), Flavonoids; Trans -Tephrostachin derivatives, Enzyme inhibition kinetics, Molecular docking and dynamics, Biochemistry, Neuroscience, Pharmacology